Bisnis Online: Peluang dan Tantangan Pemenuhan Kebutuhan Ekonomi Keluarga Masyarakat Perkotaan - Misbawati Misbawati (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2021)
Online business is the most popular and much-loved business opportunity in Indonesia today. Apart from not requiring large capital in its management, this type of business can be done by anyone, anytime, and anywhere. It's even enough to only have one or two social media accounts, business or online sales can already be done with various products. This paper discusses the opportunities and challenges of online business in fulfilling the family economy, especially urban communities in Makassar. The unit of analysis of this study is five families, each of which a wife or husband works as an online seller with different products and marketing targets. The selection of urban communities as the locus and target of the study was because the level of difficulty in the process of fulfilling the economic needs of the family was much higher than that of rural communities. Urban communities have few alternative choices of work to meet family needs due to a lot of competition, while rural communities are much more numerous and the family atmosphere is still very strong.